The Syndemic of Substance Use, High-Risk Sexual Behavior, and Violence: A Qualitative Exploration of the Intersections and Implications for HIV/STI Prevention Among Key Populations in Lagos, Nigeria - Dirisu, Osasuyi; Adediran, Mayokun; Omole, Adekemi; Akinola, Akinwumi; Ebenso, Bassey; Shoyemi, Elizabeth; Eluwa, George; Tun, Waimar; Adebajo, Sylvia (Frontiers in Tropical Diseases, 2022)
Background Key populations (KP) are defined groups with an increased risk of HIV due to specific higher risk behaviours. KP who use substances engage in risky behaviors that may play a co-active role in HIV transmission and acquisition in Nigeria. This qualitative study explored the 'syndemics' of substance use, sexual risk behavior, violence and HIV infection among KP who use substances. Methods Nineteen sexually active men who have sex with men [MSM] and 18 female sex workers [FSW] aged 16 years and older who use substances were purposively selected to participate in sixteen in-depth interviews and two focus groups. We utilized a syndemic framework to explore the interaction of socio-economic factors, substance use and high-risk sexual practices. The interviews were audio-recorded, transcribed, organized in NVIVO 11 and analyzed using thematic analysis. Results Majority (95%) were non-injection substance users (primarily alcohol and marijuana); a few KP also used cocaine and heroin. Sixty percent of participants were between 16-24 years. Substance use utilities and trajectories were heavily influenced by KP social networks. They used substances as a coping strategy for both physical and emotional issues as well as to enhance sex work and sexual activities. Key HIV/STI risk drivers in the settings of substance use during sexual intercourse that emerged from this study include multiple sexual partnerships, condom-less sex, transactional sex, intergenerational sex, double penetration, rimming, and sexual violence. Poverty and adverse socio-economic conditions were identified as drivers of high-risk sexual practices as higher sexual risks attracted higher financial rewards. Conclusions and Recommendations Findings indicate that KP were more inclined to engage in high-risk sexual practices after the use of substances, potentially increasing HIV risk. The syndemic of substance use, high-risk sexual behavior, adverse socio-economic situations, and violence intersect to limit HIV prevention efforts among KP. The behavioural disinhibition effects of substances as well as social and structural drivers should be considered in the design of targeted KP HIV prevention programs. HIV intervention programs in Nigeria may yield better outcomes if they address the nexus of sexual risk behavior and substance use as well as knowledge and appropriate use of HIV prophylaxis.